Democracy and Development in Africa: Contending Issues and Prospects for the 21st Centuries - Abdulyakeen, Abdulrasheed (Jurnal Penegakan Hukum dan Keadilan, 2023)
The study examines contentious issues related to democracy and development in Africa. Substantially relying on secondary sources of data collection to adequately reflect the issues involved in this study, an interdisciplinary approach to historical research was adopted using content analysis. The study discovered empirical evidence supporting the argument that leadership changes are frequent or uncommon. In both situations, these leaders choose to govern in countries with weak or non-existent institutions, allowing them to avoid accountability for their corrupt behavior and abuse of office. According to the study, some challenges that have slowed development are lack of accountability, transparency, and democratic government, which must be addressed realistically for progress. Making the African system run more effectively and efficiently depends on the characteristics and eccentricities of those in authority.